2022
DOI: 10.3389/fpubh.2022.1034624
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of intensive care unit nurses working with COVID-19 patients: A systematic review and meta-synthesis of qualitative studies

Abstract: ObjectivesIntensive Care Unit (ICU) nurses are at the forefront of fighting and treating the Coronavirus 2019 (COVID-19) pandemic and are often directly exposed to this virus and at risk of disease, due to their direct care for infected patients. This study aims to synthesize the experiences of ICU nurses working with COVID-19 patients.MethodsA systematic review and meta-synthesis of qualitative studies were undertaken. A systematic literature search in four databases, including Web of Sciences, Scopus, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 67 publications
(272 reference statements)
0
28
0
Order By: Relevance
“…The unknown nature of the disease also created uncertainty as the route of transmission and prognosis were not entirely clear in the early phase of the pandemic. 14 The study by Bergman et al 9 was conducted in Sweden and identified one of its themes as 'tumbling into chaos'. This theme describes how many of the nurses working during the pandemic found themselves in a chaotic and surreal environment through the creation of surge capacity in operating departments as well as staff being transferred with little or no induction and training.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 3 more Smart Citations
“…The unknown nature of the disease also created uncertainty as the route of transmission and prognosis were not entirely clear in the early phase of the pandemic. 14 The study by Bergman et al 9 was conducted in Sweden and identified one of its themes as 'tumbling into chaos'. This theme describes how many of the nurses working during the pandemic found themselves in a chaotic and surreal environment through the creation of surge capacity in operating departments as well as staff being transferred with little or no induction and training.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Uncertainty in the early stages of the pandemic is compounded by fear and anxiety among staff about becoming infected and then passing the infection on to family members. 14,15 Over time staff adapt to the challenges presented by the pandemic and, in a wide-ranging meta-synthesis exploring nurses' psychological experiences, Han et al 15 found staff gradually adapted to the work and became more confident in managing critically ill patients with COVID-19.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 It has been proven that the health of the work environments of critical care nurses affects patient care outcomes and the job satisfaction and retention of registered nurses. 5 A growing body of evidence demonstrates a connection between nurse work environments and patient outcomes. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%